2013
DOI: 10.1634/theoncologist.2012-0388
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Therapies for Advanced Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a significant cause of death worldwide. HCC is a highly vascular tumor, and proangiogenic cytokines such as vascular endothelial growth factor (VEGF), platelet‐derived growth factor (PDGF), and fibroblast growth factor may play crucial roles in this disease. Sorafenib, a multikinase inhibitor that blocks VEGF and PDGF signaling, was the first systemic therapy to demonstrate improved survival in patients with advanced HCC. Several other drugs targeting VEGF are in development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 56 publications
(58 reference statements)
0
33
0
Order By: Relevance
“…Despite improvements in diagnostic and therapeutic strategies, the prognosis of HCC still remains poor (2)(3)(4). Inhibiting angiogenesis has been used as a strategy in the treatment of HCC (5,6). For example, sorafenib, a VEGF receptor (VEGFR) inhibitor with activity against platelet-derived growth factor receptor (PDGFR), c-Kit receptor, RAF and p38 signal transduction pathways, has become a standard treatment in patients with advanced HCC (7).…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in diagnostic and therapeutic strategies, the prognosis of HCC still remains poor (2)(3)(4). Inhibiting angiogenesis has been used as a strategy in the treatment of HCC (5,6). For example, sorafenib, a VEGF receptor (VEGFR) inhibitor with activity against platelet-derived growth factor receptor (PDGFR), c-Kit receptor, RAF and p38 signal transduction pathways, has become a standard treatment in patients with advanced HCC (7).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs inhibiting VEGF biological actions are being used to treat different types of cancer, including hepatocellular carcinoma. 12 This approach has also been proposed to treat portal hypertension and attenuate liver fibrosis. 13 There are no available drugs to stimulate VEGF actions in humans, which could theoretically be beneficial in promoting hepatic fibrosis resolution.…”
mentioning
confidence: 99%
“…ZNF281 has been identified to be involved in epithelial-mesenchymal transition and cancer (33). Previous studies have demonstrated that VEGF has various effects on several types of cancer, including the promotion angiogenesis, invasion and migration (34,35). Presently, to the best of our knowledge, there are no data that associate cancer with BIVM, NPAS4 or MKLN1.…”
Section: Of Cases ---------------------------------------------------mentioning
confidence: 99%